2020
DOI: 10.3329/medtoday.v32i2.48825
|View full text |Cite
|
Sign up to set email alerts
|

Zinc as Adjunct Therapy in Neonatal Sepsis

Abstract: Introduction:Altered zinc homeostasis is an important feature of pediatric sepsis, thus raising the possibility of zinc supplementation as a therapeutic strategy in neonatal sepsis, a major source of morbidity and mortality with few therapeutic options beyond antibiotics. Its objective was to find the role of zinc as adjunct therapy in neonatal sepsis. Materials and Methods: This prospective, randomized double blind placebo controlled trial was conducted in the Department of Paediatrics, Sylhet M A G Osm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Five studies were conducted in India, 2 in Egypt, and one each in Nepal, Pakistan, Bangladesh, and Italy. The study settings included pediatric inpatient wards [25, 27, 29, 30], neonatal ICUs [18, 19, 24, 26, 28, 32], and the community [31]. The characteristics of included studies are as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were conducted in India, 2 in Egypt, and one each in Nepal, Pakistan, Bangladesh, and Italy. The study settings included pediatric inpatient wards [25, 27, 29, 30], neonatal ICUs [18, 19, 24, 26, 28, 32], and the community [31]. The characteristics of included studies are as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum sample size reported was 72 children [30] and the maximum population size was 700 children [25]. Eight [18, 19, 24-27, 29, 32] of the included studies reported the therapeutic effect of zinc supplementation, whereas only 3 studies [28, 30, 31] evaluated the preventive efficacy of the zinc supplement. We report below the preventive and therapeutic effects of zinc supplementation in neonates and young infants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations